Faceless - Simms, Kayla Ashley (Ars Medica, 2023)
Dr. Kayla Simms is a 5th year General Adult Psychiatry resident based out of McMaster University’s Waterloo Regional Campus in Ontario, Canada. She studied Arts & Sciences at the University of Guelph and completed her medical degree at the University of Ottawa. Her clinical interests include emergency and outreach psychiatry and collaborative care. She has a passion for experiential-based teaching modules and operationalizing psychiatric practice through an arts and humanities lens. In her free- time, she enjoys lane swimming, birding, and improv comedy.